STRATEGI GURU DALAM PROSES PEMBELAJARAN PADA KELAS INKLUSI DI SD TAMAN MUDA IBU PAWIYATAN YOGYAKARTA TAHUN AJARAN 2016/2017 - Zulfi Rokhaniawati (Universitas Sarjanawiyata Tamansiswa, 2017)
The purpose of research is to determine: (1) Teachers strategy in the process of learning in inclusion class. (2) The assesment system that applied in inclussion class and (3) the obtactes that found and the solution of the implementation of inclusion education. The reasearch design is descriptive research with qualitative aproach. The tecnique of collecting data that used are interview, observation, and documentation. The technique of analyzing data is done by collecting data, reducing the data, presenting the data, and drawing the conclusion. The result of the research show that (1) strategy taht applied by the teachers is making learning design, material, media and setting the the sit arrangement. (2) Assesment teachers that used is determining the criteria of minimum compliteness, decreasing indicator, and distiquishing the exercises betwen normal students and abnormal students. (3) The obstacles that teacher found there is no specific media for upnormal students, the amount of abnormal students that raise, and the variety of abnormal students, so it complicated the teachers to arranging strateg. The solutions that teacher applied is collaborating with specific teacher and sharing with other teacher and hadmaster.